Awareness of Inclusive Education Association with Students Willingness to Volunteer - Judianto, Rizqi Maharani Muthi'ah Putri; Seprina, Wa Ode (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
Inclusive education promotes equitable learning opportunities for all students, including those with disabilities. Although Indonesia has established legal frameworks supporting inclusion, such as UU No. 19/2011 and UU No. 8/2016, practical implementation remains hindered by infrastructural and sociocultural barriers. This study investigates how university students’ awareness of inclusive education influences their willingness to volunteer in inclusive initiatives, employing the Theory of Reasoned Action (TRA) as the analytical framework. Utilizing a quantitative approach, data were collected from 468 undergraduate students across 65 universities in the Greater Bandung area and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results indicate that awareness significantly influences attitudes (β=0.233), subjective norms (β=0.626), and willingness to volunteer (β=0.260), with subjective norms exerting the strongest effect on willingness (β=0.462). Furthermore, awareness indirectly enhances willingness through subjective norms. These findings underscore the critical role of social influence and informed understanding in fostering inclusive engagement, suggesting that universities should strengthen awareness-building and peer-based initiatives to promote inclusive education.